Application of Color Doppler Ultrasound Combined with Magnetic Resonance Imaging in Placenta Accreta. (13th July 2022) - Sun, Xue; Ren, Runrun; Yu, Xiaoqian; Peng, Fang; Gao, Xia
Abstract : In order to improve the diagnostic value of color Doppler ultrasonography in placenta accreta and make the diagnosis more accurate, a method to detect placenta accreta by combining color Doppler ultrasonography and magnetic resonance is proposed. The patients with placenta accreta were selected for color Doppler ultrasonography and MRI examination. Kappa test was used to analyze the consistency between the results of ultrasound and MRI examination alone and combined diagnosis and pathological examination results, and the receiver operating characteristic (ROC) was drawn. Price compliance, sensitivity, specificity, good estimate rate, negative bid success rate, and Youden index were chosen as the basis for measuring the value of our tests. The results showed that the Kappa combined test rate was 0.609, the equivalent efficiency was 80.90%, and the correlation was good; ROC curve analysis showed that the sensitivity and specificity of articular placenta accreta were 91.75% and 89.26%. The sensitivity, uniqueness, good estimate, negative predictive value, and Youden index of color Doppler ultrasound combined with magnetic resonance imaging>magnetic resonance imaging>color Doppler ultrasound in our laboratory were compared, and the difference was significant (P < 0.05 ). The experimental results show that color Doppler ultrasound and MRI are effective in the diagnosis of placenta accreta, and each has advantages and disadvantages. Therefore, it has been improved in the diagnosis of placenta accreta, is helpful for the diagnosis of placenta accreta, and is suitable for popularization and use.